Predictor variables of childbearing motivations in Brazilian women and men - Varas, Giuliana Violeta Vasquez; Borsa, Juliane Callegaro (Paidéia (Ribeirão Preto), 2021)
This study aimed to analyze the relationships between positive (PCM), negative (NCM) childbearing motivations and psychological, sociodemographic, family of origin and partner relationship variables in a sample of 1969 Brazilians (83.6% female), aged 18 to 50 years (M = 29.27; SD = 5.97). Spearman correlations, Mann-Whitney and Kruskal Wallis U-tests, and multiple regressions were performed. The results of the correlations and multiple regressions verified the relationship between both motivations and the various variables postulated. It was also verified that religiosity was the variable with greater predictive power for PCM and having or not having children was the variable with greater predictive power for NCM. In the group difference analysis, significant differences were found for PCM according to occupation, type of relationship, and presence/absence of a partner. As for the NCM, significant differences were found according to sex.